Caffeine increases myoglobin expression via the cyclic AMP pathway in L6 myotubes. Issue 9 (15th May 2021) - Yokokawa, Takumi; Hashimoto, Takeshi; Iwanaka, Nobumasa
Abstract: Myoglobin is an important regulator of muscle and whole‐body metabolism and exercise capacity. Caffeine, an activator of the calcium and cyclic AMP (cAMP)/protein kinase A (PKA) pathway, enhances glucose uptake, fat oxidation, and mitochondrial biogenesis in skeletal muscle cells. However, no study has shown that caffeine increases the endogenous expression of myoglobin in muscle cells. Further, the molecular mechanism underlying the regulation of myoglobin expression remains unclear. Therefore, our aim was to investigate whether caffeine and activators of the calcium signaling and cAMP/PKA pathway increase the expression of myoglobin in L6 myotubes and whether the pathway mediates caffeine‐induced myoglobin expression. Caffeine increased myoglobin expression and activated the cAMP/PKA pathway in L6 muscle cells. Additionally, a cAMP analog significantly increased myoglobin expression, whereas a ryanodine receptor agonist showed no significant effect. Finally, PKA inhibition significantly suppressed caffeine‐induced myoglobin expression in L6 myotubes. These results suggest that caffeine increases myoglobin expression via the cAMP/PKA pathway in skeletal muscle cells. Abstract : Myoglobin is an important regulator of muscular and whole‐body metabolism and exercise capacity. However, the detailed molecular pathway regulating the myoglobin expression remains mostly unclear. This study shows that caffeine increases myoglobin expression via the cAMP/PKA pathway in muscle cells.